The Geography of Climate Change Adaptation in Urban Africa - Cobbinah, Patrick Brandful; Addaney, Michael (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book take a comprehensive look at several cases of climate change adaptation responses across various sectors and geographical areas in urban Africa and places them within a solid theoretical context. Each chapter is a state-of-the-art overview of a significant topic on climate change adaptation in urban Africa and is written by a leading expert in the field. In addition to the focus on the geography of urban adaptation to climate in Africa, this collection offers a broader perspective by blending the use of case studies and theory based research. It examines transformations in climate change adaptation in urban Africa and its future orientation from the perspectives of urban planners, political economists, environmentalists, ecologists, economists and geographers, thereby addressing the challenges facing African cities adaptation responses from all angles. Providing up-to-date and authoritative contributions covering the key aspects of climate change adaptation in urban Africa, this book will be of great interest to policymakers, practitioners, scholars and students of geography, urban development and management, environmental science and policy, disaster management, as well as those in the field of urban planning. Patrick Brandful Cobbinah is a Lecturer in Land Use and Environmental Planning at the Department of Planning, Kwame Nkrumah University of Science and Technology, Ghana. Patrick's background is in human geography with broad experience in urban and regional planning gained through teaching and research conducted at universities in Ghana and Australia. Michael Addaney is a Senior Research Assistant at the University of Energy and Natural Resources, Sunyani, Ghana and PhD candidate at the Research Institute of Environmental Law, Wuhan University, Wuhan, China. Michael's research interests broadly focus on the role of international human rights law in framing and implementing responses to sustainability challenges in sub-Saharan Africa. .